Attempts to Avoid Traumatic Occurrences through the Posthuman in Don DeLillo’s Zero K (2016) and Kazuo Ishiguro’s Klara and the Sun (2021) - Cristina Arbués Caballé (Complutense Journal of English Studies, 2025)
Don DeLillo’s Zero K (2016) and Kazuo Ishiguro’s Klara and the Sun (2021) explore the possible outcomes on the path toward a future riddled with artificial intelligence, as they examine the role posthumanism may embody in future societies. Both texts concern themselves with the depiction of characters who attempt to avoid traumatic occurrences through the (ab)use of posthuman proceedings, as well as with the impending hierarchical (re)ordering implicit in the access to posthuman practices. DeLillo and Ishiguro portray worlds in which human beings tamper with science not yet fully explored as they depict the uncertainties that the encounter with the posthuman other entails. Concurrently, both authors theorise that privilege may be abused to avoid suffering and loss, by showcasing attempts at avoiding emotional turmoil. This way, both authors provide an exploration of the future uses posthuman practices may provide, and the possible inherent dangers implied. In so doing, both novels explore the ways in which the approach to trauma and posthumanism may be inextricably linked.